Protein disulphide isomerase inhibition as a potential cancer therapeutic strategy - Lauren E. Powell (Cancer Medicine, 2021)
Abstract The protein disulphide isomerase (PDI) gene family is a large, diverse group of enzymes recognised for their roles in disulphide bond formation within the endoplasmic reticulum (ER). PDI therefore plays an important role in ER proteostasis, however, it also shows involvement in ER stress, a characteristic recognised in multiple disease states, including cancer. While the exact mechanisms by which PDI contributes to tumorigenesis are still not fully understood, PDI exhibits clear involvement in the unfolded protein response (UPR) pathway. The UPR acts to alleviate ER stress through the activation of ER chaperones, such as PDI, which act to refold misfolded proteins, promoting cell survival. PDI also acts as an upstream regulator of the UPR pathway, through redox regulation of UPR stress receptors. This demonstrates the pro‐protective roles of PDI and highlights PDI as a potential therapeutic target for cancer treatment. Recent research has explored the use of PDI inhibitors with PACMA 31 in particular, demonstrating promising anti‐cancer effects in ovarian cancer. This review discusses the properties and functions of PDI family members and focuses on their potential as a therapeutic target for cancer treatment.